Nghiên cứu tổng hợp và cấu trúc của hai phức chất K[PtCl3(isopropyl eugenoxyaxetat)] và [PtCl(isopropyl eugenoxyaxetat-1H)]2 - Thống, Phạm Văn; Thanh Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Two organometalliccomplexes of platinum(II) K[PtCl3(iso-Preug)] (M1) and [PtCl(iso-Preug-1H)]2 (M2) have been synthesized for the first time. The structures of M1 and M2 were determined by means of platinum analysis, IR, 1H, 13C NMR spectroscopy and X-ray diffraction. In complex M1, isopropyleugenoxyacetate (iso-Preug) only coordinates with platinum(II) at ethylenic double bond of allyl group. In M2, deprotonated iso-Preug is bound up with platinum(II) both at ethylenic double bond of allyl group and at C atom of benzene ring to generate dinuclear metallacyclic complex. Keywords: Isopropyl eugenoxyacetate, platinum(II) complex, NMR